Well-Being among Academic Staff in Higher Education Institutions: A Review of Organization Support Theory (OST) and Job Demand Resources Theories (JDRs) - Mbabazi, Annet (Interdisciplinary Journal of Education, 2024)
Well-being is a multidimensional concept that reflects employees’ satisfaction with life, the prevalence of contentment and pleasure in their jobs, and in particular the emotions that the jobs provide the opportunities for employees to enhance their opportunities into self-fulfilment. This research on well-being aims to examine how job demand resources and organisation support affect employee well-being in higher education institutions. In deriving these factors of well-being, I considered two theories namely; Organization Support Theory (OST) and Job Demand Resources Theory (JDRs) to help me isolate gaps for future research. The review is in sequence. Though the paper may be of relevance to establishing the factors that influence employee well-being, it also emanates as a segment of a study in the higher education environment.